2005
DOI: 10.1080/03610730500326341
|View full text |Cite
|
Sign up to set email alerts
|

Congruence of Medication Information from a Brown Bag Data Collection and Pharmacy Records: Findings from the Seattle Longitudinal Study

Abstract: The validity of health information obtained through participants' reports of current medications (e.g., the brown bag method) is an important, but under-studied, area. In the current study, we examined the congruence of medication reports from a brown bag data collection with the pharmacy prescription records for 1430 participants (ages 23 to 97 years) of the seventh wave of the Seattle Longitudinal Study. Overall, the congruence of the brown bag data and pharmacy records was high. Congruence was better for yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 29 publications
(48 reference statements)
1
45
0
Order By: Relevance
“…However, when studying OTC drug use, not many options beyond self-reporting are available. While face-to-face studies can rely on the brown-bag method which is thought to increase comprehensiveness and accuracy of the reported use [36,37], this is not possible in the context of online surveys. Fourthly, survey research cannot be used to draw causal relationships [38].…”
Section: Discussionmentioning
confidence: 98%
“…However, when studying OTC drug use, not many options beyond self-reporting are available. While face-to-face studies can rely on the brown-bag method which is thought to increase comprehensiveness and accuracy of the reported use [36,37], this is not possible in the context of online surveys. Fourthly, survey research cannot be used to draw causal relationships [38].…”
Section: Discussionmentioning
confidence: 98%
“…The advantage of home visits is the possibility to get insight into the patient's management of his/her drug therapy at the place where it happens, and to detect DRPs which most probably would not be picked up by interviews in the pharmacy, even if the so called 'brown bag' method is used [33,34]. Therefore, we tried to identify those items of our interview guide that could only be picked up by home visits.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies are rather small and often conducted in specific populations such as participants in case-control studies or specific patient and age groups [9e11]. We have identified only two large, population-based studies comparing self-reported data on medicine use and pharmacy records [12,13].…”
Section: Introductionmentioning
confidence: 99%